The Pyrolytic Characteristics and Kinetics of Agricultural Waste, Bituminous Coal, and Their Blends - Sutcu, Hale; Piskin, Sabriye (TAYLOR & FRANCIS INC, 2011)
This study investigates the pyrolytic characteristics and kinetics of bituminous coal, vine-trimming waste, and blends of these in varying proportions. The pyrolysis of the bituminous coal and vine-trimming waste was performed at heating rates of 5 degrees C/min, 20 degrees C/min, and 80 degrees C/min under a nitrogen flow rate of 50ml/min from ambient to 1000 degrees C. Different blends containing 10%, 20%, 40%, and 50% vine-trimming waste were prepared and pyrolyzed at a heating rate of 20 degrees C/min and a nitrogen flow rate of 50ml/min from room temperature up to 1000 degrees C. The reaction degrees and kinetic parameters were calculated using the Coats and Redfern kinetic model. The pyrolysis of bituminous coal and vine-trimming waste took place in two stages, and with increasing heating rate there was a decrease in the activation energies. In contrast, the pyrolysis of the blends occurred in two stages. The first stage involves decomposition of vine-trimming waste, and the second one that of bituminous coal. As the proportion of vine-trimming waste in the blend increased, there was a decrease in the activation energy in the first stage and an increase in the second stage.
Keywords: Bituminous coal; Blend; Coats and Redfern; Heating rate; Kinetics; Pyrolysis; Thermal analysis; Vine-trimming waste; THERMOGRAVIMETRIC ANALYSIS; BIOMASS BLENDS; DEVOLATILIZATION; BEHAVIOR; STRAW; Engineering; Materials Science